Faktor-Faktor Penyebab Lama Masa Studi Mahasiswa Program Studi Pendidikan Geografi - Rika Maulina; Zulfadhli Zulfadhli; Nazaruddin Ali Basyah (Universitas Syiah Kuala, 2019)
This Study raised the issue concerning the factors causing the length of study period of the students of the Geography Education Study Program. The objectives of this study were to find out the factors causing the length of study period of the students of the Geography Education Study Program and to find out factors strongly affecting the length of study period of the students of the Geography Education Study Program. This study employed descriptive qualitative approach, while the subject of this study were students of the Geography Education Study Program of class 2011 totaling about 10 people. Data were collected through interview and documentation study, while data analysis was conducted through data reduction, data display, and conclusion drawing. This study was a qualitative study that describes the facts in the field. The results of the research showed that the factors causing the length of study period of the students of the Geography Education Study Program were 1) Physical factor that is health and 2) Psychology factors that is interest and intelligence. Meanwhile, the external factors were 1) Family environment that is family economy, 2) Campus environment that is curriculum, and 3) Social environment that is friends. From all those aspects, the campus environment had the strongest influence on the length of the study period. It was because the campus environment aspect in the lecture curriculum had a great impact on the success of the students in completing their studies.